Advantages and effectiveness of the powder metallurgy in manufacturing technologies - A. Panda (Metalurgija, 2018)
Powder metallurgy is the manufacturing science of producing solid parts of desired geometry and material from powders. Although the process has existed for more than 100 years, over the past quarter century it has become widely recognized as a superior way of producing high-quality parts for a variety of important applications. This success is due to the advantages the process offers over other metal forming technologies, advantages in material utilization, shape complexity, near-net-shape dimensional control, among others. Commonly known as powder metallurgy, it may also be referred to as powder processing considering that non-metal powders can be involved. Powders are compacted into a certain geometry then heated (sintered), to solidify the part.